ANALISIS WACANA KRITIS PADA TAGAR “PERINGATAN DARURAT” DI MEDIA SOSIAL X - Rahmawatim, Solikhah Anita; Wahyu Mulyani (ETNOLINGUAL, 2025)
Abstract: The hashtag "peringatan darurat" contains posts urging the public to monitor government decisions. This study aims to reveal the use and influence of language in the "peringatan darurat" hashtag on the social media platform X. The research employs a descriptive method with a qualitative approach. The data sources consist of tweet texts from posts tagged with "peringatan darurat" on social media X. To collect data, the methods used in this study include observation and documentation. The research analyzes microstructure, superstructure, and macrostructure using the Critical Discourse Analysis (CDA) model by Teun A. van Dijk. The microstructure is divided into semantics, syntax, and stylistics. The semantic elements reveal the use of denotative, connotative, rhetorical, and informal diction. The syntactic elements include declarative, imperative, and persuasive sentence forms. The stylistic elements highlight informative, satirical, and ironic language styles that enhance the discourse’s meaning. The superstructure identifies schematic elements, comprising an introduction, body, and conclusion. The macrostructure uncovers thematic elements that illustrate social criticism, collective solidarity, and public participation. The dimension of power reflects resistance to government policies through critical language, while the ideological dimension emphasizes the values of democracy and social justice underlying public opinion. This study concludes that the discourse within the "peringatan darurat" hashtag is strategically constructed in accordance with the ideological interests of the actors involved. The account @antikorupsi exerts pressure on the government through factual arguments, @walhinasional highlights environmental exploitation using metaphors, @aingriwehuy conveys public concerns through satire, and @Penyair_Berdiri generates social pressure through emotional rhetoric. Keywords: Critical Discourse, Peringatan Darurat Hashtag, X Social Media